2003
DOI: 10.1063/1.1537868
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized growth of single crystals of nanopores

Abstract: Growth of InP self-assembled quantum dots on strained and strain-relaxed In x ( Al 0.6 Ga 0.4 ) 1 − x P matrices by metal-organic chemical vapor depositionThe role of arsine in the self-assembled growth of In As ∕ Ga As quantum dots by metal organic chemical vapor deposition Self-organized single crystalline two-dimensional hexagonal arrays of pores in InP semiconductor compound are reported. We show that the self-arrangement of pores can be obtained on n-type substrates with ͑100͒ and ͑111͒ orientations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 13 publications
1
74
0
1
Order By: Relevance
“…Íåëüçÿ íå óïîìÿíóòü î âîçðàñòàþùåì èíòåðåñå ê ïîðèñòîìó ôîñôèäó èíäèÿ, êîòîðûé îáëàäàåò íåîáû÷íûìè îïòè-÷åñêèìè è ýëåêòðè÷åñêèìè ñâîéñòâàìè ïî ñðàâ-íåíèþ ñ ìîíîêðèñòàëëè÷åñêèì. Ýòîìó âîïðîñó ïîñâÿòèëè ñâîå âíèìàíèå íåìàëî ó÷åíûõ [1][2][3][4][5][6][7].…”
Section: ââåäåíèåunclassified
“…Íåëüçÿ íå óïîìÿíóòü î âîçðàñòàþùåì èíòåðåñå ê ïîðèñòîìó ôîñôèäó èíäèÿ, êîòîðûé îáëàäàåò íåîáû÷íûìè îïòè-÷åñêèìè è ýëåêòðè÷åñêèìè ñâîéñòâàìè ïî ñðàâ-íåíèþ ñ ìîíîêðèñòàëëè÷åñêèì. Ýòîìó âîïðîñó ïîñâÿòèëè ñâîå âíèìàíèå íåìàëî ó÷åíûõ [1][2][3][4][5][6][7].…”
Section: ââåäåíèåunclassified
“…13 Hamamatsu et al 17 succeeded in electrochemically forming arrays of straight nanopores without branches on n-InP͑001͒ substrates. The self-assembled formation of hexagonal arrays of pores were later reported by Fujikura et al 18 and Langa et al, 19 where the pores were laterally separated by InP nanowalls and were formed along a straight vertical direction over a distance of approximately 1-100 m. Such close-packed nanostructures have extremely large surface areas ͑i.e., over 10 m 2 /cm 3 ͒ compared with the semiconductor surfaces prepared by conventional methods used in the semiconductor industry such as lithography and dry etching, vacuum evaporation, and epitaxial growth. Merchant et al 21 recently reported that the InP nanowalls between each pore show proper conductivity and carrier mobility.…”
mentioning
confidence: 91%
“…8,9 Of these, the semiconductor porous nanostructures formed by electrochemical anodization are one of the more promising candidates for use as the building blocks of biochemical sensors. The direct formation of porous structures has been investigated for various materials such as Si, 10,11 GaAs, 12,13 GaP, 14,15 InP, [16][17][18][19] GaN, 20 and CdSe. 13 Hamamatsu et al 17 succeeded in electrochemically forming arrays of straight nanopores without branches on n-InP͑001͒ substrates.…”
mentioning
confidence: 99%
“…The material is used, for instance, as tamplate for the formation of metallic nonorods (3,4). Another example is the electrochemical preparation of homogeneous pore arrays on InP (5, 6) suggested for photonic band gap applications (7,8). More complex structures are observed during initial stages of porous silicon formation on Si(111) using rather different preparation conditions: mesa-type features with side faces being exclusively {111}, {110} and {113} oriented (9,10).…”
Section: Introductionmentioning
confidence: 99%